2021
DOI: 10.31729/jnma.7045
|View full text |Cite
|
Sign up to set email alerts
|

Compliance of WHO Surgical Safety Checklist at a Pediatric Surgical Unit in a Tertiary Level Hospital: A Descriptive Cross-sectional Study

Abstract: Introduction: The Surgical safety checklist by World Health Organization has been used for the last two decades. There is every chance of unwanted expected disasters in Operating-Room in Pediatricsurgical cases. Our study is to observe the utilization of the safety checklist and evaluate occurrence of never-events in Tertiary Level Pediatric Surgery Unit in Nepal. Methods: A descriptive cross-sectional study was done at Nepal Medical College Teaching Hospital from January 2021-June 2021 with record-based data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The benefits of following the SSC during surgical procedures seem to be dampened by partial compliance, with limited evidence that the risk of complications is positively associated with checklist incompleteness and unidentified non‐conformities (NCs) 9,20 . However, studies that examine factors associated with the risk of NCs, when identified, are lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of following the SSC during surgical procedures seem to be dampened by partial compliance, with limited evidence that the risk of complications is positively associated with checklist incompleteness and unidentified non‐conformities (NCs) 9,20 . However, studies that examine factors associated with the risk of NCs, when identified, are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The benefits of following the SSC during surgical procedures seem to be dampened by partial compliance, with limited evidence that the risk of complications is positively associated with checklist incompleteness and unidentified non-conformities (NCs). 9,20 However, studies that examine factors associated with the risk of NCs, when identified, are lacking. The objective of this study was to conduct such an investigation using data from a local health unit (LHU) in Italy that spans the 4-year period 2018-2021.…”
Section: Introductionmentioning
confidence: 99%